RARE PRESENTATION OF A GIANT INTERNAL CAROTID ARTERY (ICA) ANEURYSM CAUSING HYPOPITUITARISM - Naidu, Tharani; Abbas, Sharifah Syahirah Syed; Rajakumar, Radhamani; Samsuddin, Syahrizan (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Pituitary insufficiency secondary to giant internal carotid artery (ICA) aneurysms are rare. It is, however, an important differential to consider in cases of hypopituitarism as prompt diagnosis and treatment is necessary to prevent a fatal outcome. CASE We present a case of hypopituitarism with hyperprolactinemia secondary to a suprasellar giant ICA aneurysm. A 60-year-old female presented with bilateral visual field defects. Examination showed left temporal hemianopia and right inferior scotoma. Her cranial CT revealed a well-defined, rounded lesion arising from the suprasellar region. She was then referred for a brain and pituitary MRI. While awaiting the date of her MRI appointment, she developed diarrhoea and increasing lethargy. Pituitary hormone panel done demonstrated panhypopituitarism with hyperprolactinemia: cortisol 12 nmol/L (normal range 185-624), TSH 1.238 mU/L (0.34-5.6) free T4 6.8 pmol/L (7.9-4.4), FSH 2.2 mU/ml (2.5-10.2), LH 0.2 mU/ml (15.9-54), prolactin 1400 u/ml (<500) and GH 0.11 Ug/L (0.077-5.0). The hyperprolactinemia was attributed to the stalk compression effect. She was given hydrocortisone and thyroxine replacement. MRI revealed a sellar and suprasellar mass suggestive of a distal right ICA aneurysm. The findings were confirmed by digital subtraction angiography. Cerebral stenting was successfully performed. One month postoperatively, she has not shown any recovery of pituitary function. CONCLUSION We described an unusual case of a suprasellar giant ICA aneurysm leading to pituitary insufficiency. ICA aneurysms, particularly those located at the sellar-suprasellar region, are very rare. However, since they resemble pituitary tumours in terms of imaging and laboratory findings, an accurate diagnosis must be made in order to institute necessary treatment strategies among these patients.